SEASONAL CHANGES ON BOVINE BULK TANK MILK QUALITY FROM THREE REGIONS IN MACEDONIA - Santa, D., Nakov, D., Srbinovska, S., Trajcev, M. (Faculty of Agriculture, Goce Delcev University - Stip, 2018)
The aim of this study was to give an overview of the milk quality parameters and to investigate variations of milk composition, Somatic Cells Counts (SCC) and Total Bacteria Counts (TCC) by season of year and region of milk collection. The present study was conducted during the period of eight months in three regions in Republic of Macedonia: Berovo, Pehcevo and Delcevo. Raw bulk tank milk samples were collected from the selected dairy factories. The correlation between observed parameters was calculated with Pearson’s coefficient of correlation using all data. All results of the research were processed using one-way analysis of variance (ANOVA). The Pearson’s coefficient of correlation showed that there was statistical significant interdependence at level p<0.01 between region of collected milk and fat content, raw milk temperature and acidity level and total bacteria count. Statistical significant correlation existed between months in year when milk samples were collected and content of dry matters and proteins, raw milk temperature, specific gravity and acidity level. There was found statistical significant difference (p<0,001) in fat, dry matter and protein content, the presence of added water, mean raw milk temperature, specific gravity and milk acidity level between regions where milk samples were taken. The contents of fat, dry matter and protein, the presence of added water, mean raw milk temperature, specific gravity and milk acidity level were statistically significant differed (p<0,001) dependent from months in year when milk samples were taken. The other milk quality characteristics did not differ dependent from months in year.
Keywords: Raw milk composition, somatic cell count, bacteriological quality